2023
DOI: 10.1136/jnis-2022-020005
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic non-stenotic carotid disease: current challenges and opportunities for diagnosis and treatment

Abstract: Symptomatic non-stenotic carotid plaques (SyNC) are an under-researched and under-recognized source of stroke. Various imaging markers of non-stenotic carotid plaques that are associated with stroke risk have been identified, but these causal relationships need to be confirmed in additional prospective studies. Currently, there exists neither a standardized SyNC definition nor a dedicated set of imaging protocols, although researchers have started to address these shortcomings. Moreover, many neuroradiologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Various potential thromboembolic sources, including cardiac valvular abnormalities, covert atrial fibrillation, paradoxical embolism or arterio-arterial emboli fall under the ESUS rubric [ 2 ]. Using the TOAST criteria, large artery atherosclerosis (LAA) as the cause of stroke only applies if there is more than 50% luminal narrowing of the ipsilateral internal carotid artery [ 3 ]; however, non-stenotic carotid disease, defined as < 50% luminal narrowing of the internal carotid artery, can be an underlying source of emboli and cause of ischemic stroke and yet these patients are still classified as cryptogenic stroke or ESUS [ 4 ]. A systematic review showed a prevalence of non-stenotic carotid disease of 51% in patients with ischemic stroke [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various potential thromboembolic sources, including cardiac valvular abnormalities, covert atrial fibrillation, paradoxical embolism or arterio-arterial emboli fall under the ESUS rubric [ 2 ]. Using the TOAST criteria, large artery atherosclerosis (LAA) as the cause of stroke only applies if there is more than 50% luminal narrowing of the ipsilateral internal carotid artery [ 3 ]; however, non-stenotic carotid disease, defined as < 50% luminal narrowing of the internal carotid artery, can be an underlying source of emboli and cause of ischemic stroke and yet these patients are still classified as cryptogenic stroke or ESUS [ 4 ]. A systematic review showed a prevalence of non-stenotic carotid disease of 51% in patients with ischemic stroke [ 5 ].…”
Section: Introductionmentioning
confidence: 99%